Enhanced Fatty Acid Synthesis Leads to Subset Imbalance and IFN-γ Overproduction in T Helper 1 Cells - Iwata, Shigeru; Zhang, Mingzeng; Hao, He; Trimova, Gulzhan; Hajime, Maiko; Miyazaki, Yusuke; Ohkubo, Naoaki; Satoh Kanda, Yurie; Todoroki, Yasuyuki; Miyata, Hiroko; Ueno, Masanobu; Nagayasu, Atsushi; et al. (Frontiers in Immunology, 2020)
Recent reports have shown the importance of IFN-γ and T-bet+ B cells in the pathology of SLE, suggesting the involvement of IFN-γ-producing T-bet+ CD4+ cells, i.e., Th1 cells. This study determined the changes in Th1 subsets (T-bet+FoxP3± cells) with metabolic shift and their potential as therapeutic targets in SLE. Compared with healthy donors, patients with SLE had higher numbers of T-bethiFoxp3- effector cells and T-bet+Foxp3lo non-suppressive cells, which excessively produce IFN-γ, and lower number of non-IFN-γ-producing T-bet+Foxp3hi activated-Treg cells. These changes were considered to be involved in treatment resistance. The differentiation mechanism of Th1 subsets was investigated in vitro using memory CD4+ cells obtained from healthy donors and patients with SLE. In memory CD4+ cells of healthy donors, both rapamycin and 2-deoxy-D-glucose (2DG) suppressed T-bet+Foxp3- cells, and induced T-bet+Foxp3+(lo/hi) cells. Rapamycin induced IFN-γ-producing T-bet+Foxp3lo cells accompanied with enhanced lipid metabolism, whereas 2DG induced IFN-γ-non-producing T-bet+Foxp3hi cells. In memory CD4+ cells of SLE patients, inhibition of fatty acid synthesis, but not β-oxidation, suppressed IFN-γ production and replaced T-bet+Foxp3lo cells with T-bet+Foxp3hi cells. Metabolic regulators such as fatty acid synthesis inhibitors may improve the pathological status by correcting Th1 subset imbalance and overproduction of IFN-γ in SLE.